Qualitative Assessment of Speech Perception Performance of Early and Late Cochlear Implantees - Kant, Anjali R. (Indian J Otolaryngol Head Neck Surg, 2015)
The present study aims to provide a qualitative description and comparison of speech perception performance using model based tests like multisyllabic lexical neighborhood test (MLNT) and lexical neighborhood test (LNT), in early and late implanted (prelingual) hearing impaired children using cochlear implants. The subjects comprised of cochlear implantees; Group I (early implantees)—n = 15, 3–6 years of age; mean age at implantation—3½ years. Group II (late implantees)—n = 15, 7–13 years of age; mean age at implantation—5 years. The tests were presented in a sound treated room at 70 dBSPL. The children were instructed to repeat the words on hearing them. Responses were scored as percentage of words correctly repeated. Their means were computed. The late implantees achieved higher scores for words on MLNT than those on LNT. This may imply that late implantees are making use of length cues in order to aid them in speech perception. The major phonological process used by early implantees was deletion and by the late implantees was substitution. One needs to wait until the child achieves a score of 20 % on LNT before assessing other aspects of his/her speech perception abilities. There appears to be a need to use speech perception tests which are based on theoretical empirical models, in order to enable us to give a descriptive analysis of post implant speech perception performance.